(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article highlights data on the impact of processing rice grains with biofertilizers of the newly created medium-ripened variety "Sadaf", bringing the planting rates to 4,5,6 million grains /ha on germination, germination of grains and density of seedlings when they are placed in field conditions.